Efeito do Estresse Térmico Agudo sobre os Níveis da Proteína e RNA Mensageiro da HSP70, em Fígado e Cérebro de Pintos de Corte de Diferentes Linhagens - Dionello, Nelson José Laurino; Ferro, Jesus Aparecido; Macari, Marcos [UNESP]; Rutz, Fernando; Furlan, Luiz Roberto [UNESP]; Ferro, Maria Inês Tiraboschi (My University, 2001)
Eighty broiler chicks, Naked neck (Na/na) and Hubbard-Pettersen strains, were exposed to acute heat stress (36-37°C), from 2 to 5 days of age, and body weight and cloacal temperature were measured in the beginning and at the end of the heat stress period (5 h). Birds were sacrificed at the end and liver and brain samples were collected and analyzed using Western Blotting and Northern Blotting to quantify Hsp70 levels and mRNA Hsp70 transcript, respectively. The brain tissue had higher Hsp70 level than liver tissue. Before heat stress it was not observed difference in the Hsp70 expression between strains. After heat stress in the liver it was observed in increase in the Hsp70 level (naked neck birds at 4 and 5 days), and in the brain a reduced Hsp70 level was found when compared with the control birds (Naked neck birds at 2 days). The size of the mRNA Hsp70 transcript was 2.7 kb. The data of this experiment suggest that to the brain tissue heat stress affect Hsp70 at transcriptional and translational levels, and for hepatic tissue the effect is only at translational level, for different lines.
Effect of Acute Heat Stress on Hepatic and Cerebral Messenger RNA Heat Shock Protein 70 and Heat Shock Protein 70 Level of Broiler Chicks from 2 to 5 Days Old of Different Strains
Keywords: Acute heat stress; Hepatic and brain Hsp70; Northern Blotting and Western Blotting; Protein and mRNA Hsp70